Phytochemical Analysis of Iypathi Chooranam - K. Ramya; P. Karthik; K. Shyamala; T. Maharasi Maniselvi (International Journal of Ayurveda and Pharma Research, 2025)
Iypathi Chooranam is a traditional polyherbal formulation used in the Siddha system of medicine, reputed for its therapeutic efficacy in managing ailments such as fever, skin disorders, gastrointestinal disturbances, eye diseases. The present study aims to evaluate the phytochemical profile of Iypathi Chooranam through preliminary screening techniques to establish its pharmacological potential. The formulation was prepared as per classical Siddha texts Agasthiyar nayana vithi and subjected to successive extraction using solvents of increasing polarity hexane, ethyl acetate, ethanol, and water. Each extract was then analyzed for the presence of major phytoconstituents, including alkaloids, flavonoids, tannins, saponins, glycosides, terpenoids, and phenolic compounds, using standard qualitative phytochemical methods. The results revealed the compounds known for their antioxidant, antimicrobial, and anti-inflammatory properties. The presence of alkaloids and saponins further supports the traditional claims of its therapeutic efficacy. This phytochemical profiling provides a foundational understanding of Iypathi Chooranam bioactive potential and supports its continued use in traditional medicine. This research contributes to the growing scientific validation of Siddha formulations and supports their integration into evidence-based complementary medicine. This analysis helps to explore the properties of medicine in their usage in clinical studies. It is concluded that the presence of certain phytochemicals justifies the better use of the medicine Iypathy chooranam for eye diseases.